Removal of biocontamination in the food industry using physical methods; an overview. (June 2023) - Dallagi, Heni; Jha, Piyush Kumar; Faille, Christine; Le-Bail, Alain; Rawson, Ashish; Benezech, Thierry
Abstract: In the food industry, equipment surfaces with microbial entities can easily contaminate the food being processed, thereby leading to significant economic problems and even public health issues. To ensure the hygiene of materials in contact with food, cleaning processes are commonly implemented. Conventional strategies used for biofilm removal are energy and water intensive processes. Besides, they also use a substantial amount of chemicals. However, despite the strong enforcement of the conventional cleaning processes, each year, alarming statistics are reported by sanitary organizations, emphasizing the need of improving the safety and hygiene of equipment surfaces. Therefore, the investigation of strategies to effectively remove biofilm biomass is becoming essential. This literature review aims to describe the effectiveness of different physical strategies for biofilm biomass removal. Along with conventional physical methods (conventional CIP, water jet, and static foam cleaning) widely used in the food industry, other promising methods such as pulsed flow, bubble flow, foam flow, ice pigging, snow CO2, electromagnetic methods, plasma, and air jet were reported. Further, the principles, cleaning mechanisms, important process parameters, as well as, limitations associated with these methods have been discussed. All of these methods have shown a promising ability to remove biofilm, while some of them like foam flow and pulsed flow were found to be eco-friendly as they reduced environmental impacts based on LCA analyses. Graphical abstract: Image 1